1 Type I Interferon Is Necessary and Sufficient for Alloimmunization to Transfused KEL-Expressing RBCs in Mice. (11th January 2018) - Gibb, David; Liu, Jingchun; Natarajan, Prabitha; Santhanakrishnan, Manjula; Madrid, David; Eisenbarth, Stephanie; Zimring, James; Iwasaki, Akiko; Hendrickson, Jeanne
Abstract: Alloantibodies against non-ABO red blood cell (RBC) antigens cause clinically significant hemolytic events and limit the availability of RBC products, resulting in anemia-associated morbidity and mortality. Multiple human and animal studies have established that certain inflammatory disorders and inflammatory stimuli promote alloimmune responses to RBC antigens. However, molecular mechanisms underlying these findings have only been partially characterized. Given that type I interferons (IFNα/β) are induced in inflammatory conditions associated with increased alloimmunization, we tested the hypothesis that IFNα/β regulates alloimmune responses to RBC antigens. To this end, we developed a new transgenic mouse model that expresses the human KEL glycoprotein on murine RBCs (KEL RBCs). Following transfusion of KEL RBCs, WT mice produced anti-KEL IgG alloantibodies (peak response mean MFI = 50.4 ± 13.3, standard error). However, mice lacking the receptor for IFNα/β (IFNAR1 –/– ) failed to produce anti-KEL IgG in 3/3 experiments (MFI = 4.2 ± 1.7, P < .01). In addition, compared to chimeric mice lacking IFNAR1 expression on non-hematopoietic cells, T cells, or dendritic cells; the anti-KEL response of chimeric mice lacking IFNAR1 expression in all hematopoietic cells or specifically in B cells was greatly diminished in 3/3 experiments. (MFI = 3.8 ± 0.66 and 5.4 ± 1.6, respectively, compared to control chimeras, MFI = 79.8 ± 30.1, P < .05). These results indicated that IFNα/β production might also be required for alloimmunization. Thus, we also assessed alloimmune responses of mice lacking critical mediators of IFNα/β gene expression. Following transfusion in the presence of an inflammatory stimulus, double-stranded RNA, WT mice and mice lacking Toll-like receptor signaling produced comparable levels of IFNα/β and anti-KEL IgG (IgG MFI = 108 ± 25 and 162 ± 33, respectively). In contrast, mice lacking the mitochondrial antiviral signaling protein (MAVS) or the IFNα/β transcription factors, interferon regulatory factors (IRF) 3 and IRF7, produced diminished levels of IFNα/β and anti-KEL IgG in 3/3 experiments (MAVS –/– MFI = 14.7 ± 6.1, IRF3/7 -/- MFI = 5.8 ± 3.0, P < .05 compared to WT). Further, we found that co-transfusion of KEL RBCs with IFNα, in the absence of an adjuvant, was sufficient to promote RBC alloimmunization. Collectively, these results demonstrate that IFNα/β induction in the peritransfusion period and IFNAR signaling in B cells critically regulate RBC alloimmune responses in our murine model. These findings provide a potential mechanistic basis for past observations of inflammation-induced alloimmunization. They also raise the possibility that patients with IFNα/β-mediated conditions, including autoimmunity and viral infections, may have an increased risk of RBC alloimmunization and may benefit from personalized transfusion protocols and/or targeted therapies.